Development, validation and regulatory acceptance of improved purification and simplified quality control of [13N] Ammonia - Daniel L. Yokell; Peter A. Rice; Ramesh Neelamegam; Georges El Fakhri (SpringerOpen, 2020)
Abstract Background [13N]Ammonia is a cyclotron produced myocardial perfusion imaging agent. With the development of high-yielding [13N]ammonia cyclotron targets using a solution of 5 mM ethanol in water, there was a need to develop and validate an automated purification and formulation system for [13N]ammonia to be in a physiological compatible formulation of 0.9% sodium chloride since there is no widely available commercial system at this time. Due to its short half-life of 10 min, FDA and USP regulations allow [13N]ammonia to be tested in quality control (QC) sub-batches with limited quality control testing performed on the sub-batches for patient use. The current EP and the original USP method for the determination of the radiochemical purity and identity of [13N]ammonia depended on an HPLC method using a conductivity detector and a solvent free of other salts. This HPLC method created issues in a modern cGMP high volume PET manufacturing facility where the HPLC is used with salt containing mobile phase buffers for quality control analysis of other PET radiopharmaceuticals. Flushing of the HPLC system of residual salt buffers which may interfere with the [13N]ammonia assay can take several hours of instrument time. Since there are no mass limits on [13N]ammonia, a simplified TLC assay to determine radiochemical identity and purity could be developed to simplify and streamline QC. Results We have developed and validated a streamlined automated synthesis for [13N]ammonia which provides the drug product in 8 mL of 0.9% sodium chloride for injection. A novel radio-TLC method was developed and validated to demonstrate feasibility to quantitate [13N]ammonia and separate it from all known radiochemical impurities. Conclusions The process for automated synthesis of [13N]ammonia simplifies and automates the purification and formulation of [13N]ammonia in a cGMP compliant manner needed for high-throughput manufacture of [13N]ammonia. The novel radio-TLC method has simplified [13N]ammonia quality control (QC) and now enables it to be tested using the same QC equipment as [18F]fludeoxyglucose (FDA/USP recognized name for 2-[18F]fluoro-2-deoxy-D-glucose). Both the streamlined automated synthesis of [13N]ammonia and the novel radio-TLC method have been accepted and approved by the US Food and Drug Administration (FDA) for the cGMP manufacture of [13N]ammonia.